Challenges in the Implementation of Gerakan Desa Wawasan Programme in Developing Rural Areas in Sabah - Nur Shaslinda Abdul Kadir; Ubong Imang; Colonius Atang (Penerbit Universiti Pendidikan Sultan Idris, 2018)
The transformation of rural development strategies has shifted from the phases of emphasizing physical development to human capital-oriented through the Gerakan Desa Wawasan (GDW) programme. This study was conducted to assess the implementation of the GDW programme implemented in Sabah. This study uses a qualitative approach, primary data collected through an in-depth interview between the Community Development Department Officer (KEMAS) to obtain information on the implementation of the GDW programme based on the perspective of the implementer acting as the coordination of GDW. In addition, secondary data is also referred to get the information on GDW implementation in Sabah. The study found that there was a difference between Peninsular Malaysia and Sabah in developing rural areas. Among the challenges implemented in the GDW programme in Sabah found in the study were weaknesses in the selection of JKKK, village power overlapping, federal and state power overlapping, reliance on government assistance in development, JKKK appointment was not clear and lack of allocation grants. In conclusion, rural development programmes such as GDW in Sabah face various challenges to be implemented based on the perspective of the implementer, the Community Development Department (KEMAS).